2018
DOI: 10.1139/cjfas-2017-0035
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating evidence for alternative natural mortality and process error assumptions using a state-space, age-structured assessment model

Abstract: State-space models explicitly separate uncertainty associated with unobserved, time-varying parameters from that which arises from sampling the population. The statistical aspects of formal state-space models are appealing and these models are becoming more widely used for assessments. However, treating natural mortality as known and constant across ages continues to be common practice. We developed a state-space, age-structured assessment model that allowed different assumptions for natural mortality and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…The model adds to the growing evidence that multiple, simultaneously acting mortality rates may be estimated when observations of the number of mortalities are combined with observations of abundance in a population model. A common approach to fitting population models, especially in fisheries stock assessments, is to assume that natural mortality cannot be estimated and set it to a constant, externally estimated value, but evidence from hierarchical modeling indicates that more information about natural mortality rates can be derived from harvest and abundance data than was previously recognized (Millar and Meyer 2000;Miller and Hyun 2018). Using simulations, we demonstrated that it was possible to extract both entrainment and natural mortality rates, coefficients, and process variance (see Appendix A).…”
Section: Discussionmentioning
confidence: 99%
“…The model adds to the growing evidence that multiple, simultaneously acting mortality rates may be estimated when observations of the number of mortalities are combined with observations of abundance in a population model. A common approach to fitting population models, especially in fisheries stock assessments, is to assume that natural mortality cannot be estimated and set it to a constant, externally estimated value, but evidence from hierarchical modeling indicates that more information about natural mortality rates can be derived from harvest and abundance data than was previously recognized (Millar and Meyer 2000;Miller and Hyun 2018). Using simulations, we demonstrated that it was possible to extract both entrainment and natural mortality rates, coefficients, and process variance (see Appendix A).…”
Section: Discussionmentioning
confidence: 99%
“…These biases could affect stock management as they result in biased reference point estimates on both absolute and relative scales. Assuming a known natural mortality fixed as constant over time and sometimes ages is a common approach used in stock assessment (Johnson et al, ; Lee, Maunder, Piner, & Methot, ; Miller & Hyun, ). It is therefore important to know that, despite a fit to observed data that could be perceived as reasonable (Figure ), misspecifications of natural mortality can affect the perception of fish stock status irrespective of harvest history (EM3 and EM4 had large bias for both constant and varying F), and the consequences of these changes in perception on catch advice can be great.…”
Section: Discussionmentioning
confidence: 99%
“…The maximum bias was on the variance of the process errors on fish abundance (≃−30%), larger than bias in recruitment process error standard deviation (≃−3%). Underestimating process error variances is common in simulation testing and larger underestimation of variance in process errors on fish abundance compared to recruitment was also observed in state‐space single species models (Miller & Hyun, ). Auger‐Méthé et al () demonstrated that estimation bias can occur when observation errors are larger than process errors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Distinguishing recruitment process and observation error is important for 89 accurately detecting regime shifts (King et al 2015;Maunder and Thorson 2019). such as abundance and fishing mortality as random effects have been developed and is 92 effective at separately estimating process and measurement errors (Nielsen and Berg 93 2014;Miller and Hyun 2017;Okamura et al 2018). However, these models are 94 age-structured and not possible to apply to the Japanese flying squid, because its 95 life-span is a single year.…”
Section: Introduction 43mentioning
confidence: 99%